(3aVGFd GdEScfOQjIs - (3CHh Ydj GdMSf Hf YeQ Hf CHj ESMGb Hf GdMSjf GdUHGZs
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe YR GdOjf CHh GdbGSe YHO Gddg Hf GdMSjf Hf YHO Gddg Hf QhGMI GdCfUGQi dGMehi , bQGAI Ydjg hCfG GSeY , ai NGeS ThGd SfI NeS hKdGKjf hSJeGFI HMdH GdeMQhSI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B24 - (3U(B36s
(3fSNI YdjgG SeGYGJ cKjQI hUhQ SeGYGJ eNJdaI efbhdI ef fSNI GdCUds
(3hHChdgG NW YdGeI jhSa Hf YHO GdgGOi HGdSeGYs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B113 s
Keywords: (3GdJGQjNs